Dignity of Iranian Women with Breast Cancer: A Qualitative Study - Farkhondeh Sharif; Zohreh Khoshnood; Marion Eckert; Marzieh Helal Birjandi; Samaneh Bagherian (Kerman University of Medical Sciences, 2023)
Background: Respecting the human dignity of patients is one of the most important ethical requirements of the medical and nursing profession. Respect for dignity in all patients, especially in patients with breast cancer, is important because of the profound and lasting effects of this disease on patients. This study aimed to understand the perspective of patients with breast cancer on the concept of patient dignity from June 2020 to December 2020 in Iran Mehr Hospital (Radiotherapy and Oncology Center) in Birjand. Methods: This study was conducted using a qualitative approach. The data were collected through semi-structured individual interviews and analyzed using qualitative content analysis. The data were saturated after interviewing 16 patients with breast cancer who were selected using purposive sampling from June 2020 to December 2020. The main interview question was, "What does 'dignity' mean to you based on your experiences during your time with cancer?" The data elicited from the interviews were analyzed using content analysis via MAXQDA 2012 software.Results: Analysis of the patients' statements and experiences of maintaining dignity revealed three main themes. The first main theme was respect for human values, which included the subthemes of personal privacy, avoiding curiosity, confidentiality of information, and use of same-sex caregivers. The second main theme was psychological support, which included the subthemes of spousal and family empathy and support, understanding the patient's concerns and preoccupations, resentment of pity, and disclosing cancer diagnosis. The third main theme was socioeconomic support, which included the subthemes of spousal and family financial support, financial aid by support organizations, and community awareness.Conclusion: Receiving care by respecting dignity is the right of every patient. Since patients with cancer are more vulnerable, it can be argued that maintaining the dignity of these patients is more important than other patients due to the nature of the disease and the long-term involvement of patients with the disease.